Tingkat Partisipasi Masyarakat dalam Pengadaan Jamban Keluarga melalui Community Lead Total Sanitation - Jonneri Masli, Agus Suwarni, Suharman (Fakultas Kedokteran Universitas Gadjah Mada, 2010)
Background: The coverage of family toilet at Sub District of Panti is still relatively low (20.28%), morbidity from diarrhea is relatively high (8.89%) and outbreak sometimes occurs in this area. An effort that has been made by Pasaman District Health Office to widen the coverage of family toilet and minimize morbidity from diarrhea at Sub District of Panti is encouraging community participation in the provision of family toilet through Community Lead Total Sanitation (CLTS). However, the result is still far from the expectation. This may be due to limited knowledge, attitude, education, income and participation of the community in the provision of family toilet through CLTS.Objectives: To identify factors related to community participation in the provision of family toilet through CLTS at Sub District of Panti, District of Pasaman.Methods: This was a quantitative approach research cross sectional design. Location of the study was Subdistrict of Panti, District of Pasaman. Subject of the study were heads of the family participating in CLTS activities. The variable employed in this research of knowledge, attitude, education, and income; and was community participation in the provision of family toilet through CLTS. Data analysis used univariable, bivariable with chi square and multivariable with logistic regression.Results: The result of the study showed that there was relationship between knowledge, attitude and income of respondents and participation (p<0.05), whereas education had no relationship with participation (p>0.05). Out of the three factors related to community participation in the provision of family toilet through CLTS, attitude was most dominant with p=0.000 and â=0.273 and OR=5.3.Conclusion: Knowledge, attitude and income of respondents had significant relationship with community participation in the provision of family toilet through CLTS and attitude was the most dominant.Keywords: participation, community lead total sanitation, family toilet